INTEGRATING MAKASSAR ORAL LITERATURE INTO CONTEXTUAL LEARNING TO STRENGTHEN SUSTAINABLE DEVELOPMENT EDUCATION - Abd. Rahim; Nursalam Nursalam; Kasma F Amin; Fadhl Mohammed Awadh Gharamah; Andi Fatimah Yunus; Nurindah Purnama Sari (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
Makassar oral literature is a form of cultural heritage that embodies important values such as unity, humanity, courage, loyalty, commitment, and historical awareness, all of which are relevant to the concept of sustainable education. However, the utilization of oral literature as a contextual learning resource in schools remains limited, which hinders the potential for students to engage with and learn from these cultural narratives that can enhance their understanding of sustainable education values. This study aims to analyze the integration of Makassar oral literature into the Contextual Teaching and Learning (CTL) model to instill sustainable education values in students. The study employs a mixed-methods approach with a descriptive design through the analysis of Makassar oral literature texts and their application in the learning process. Data were obtained from several forms of oral literature, namely sinrilik, pappasang, kelong, and paruntu kana, which were analyzed to identify sustainable education values and their relevance within contextual learning. The results show that adding Makassar oral literature to the CTL model helps students learn more about local history, become more aware of the need to protect culture, and internalize values like humanity, commitment, courage, and loyalty. These results suggest that oral literature–based learning has the potential to serve as an innovative approach that integrates character education, local cultural heritage, and the principles of education for sustainable development in schools.